Hesperidin Ameliorates Dexamethasone-Induced Osteoporosis by Inhibiting p53 - Zhang, Meng; Chen, Delong; Zeng, Ning; Liu, Zhendong; Chen, Xiao; Xiao, Hefang; Xiao, Likang; Liu, Zeming; Dong, Yonghui; Zheng, Jia (Frontiers in Cell and Developmental Biology, 2022)
Osteoporosis is one of the most frequent skeletal disorders and a major cause of morbidity and mortality in the expanding aging population. Evidence suggests that hesperidin may have a therapeutic impact on osteoporosis. Nevertheless, little is known about the role of hesperidin in the development of osteoporosis. Bioinformatics analyses were carried out to explore the functions and possible molecular mechanisms by which hesperidin regulates osteogenic differentiation. In the present study, we screened and harvested 12 KEGG pathways that were shared by hesperidin-targeted genes and osteoporosis. p53 signaling pathway was considered to be a key mechanism. Our in vitro results showed that hesperidin partially reversed dexamethasone-induced inhibition of osteogenic differentiation by suppressing the activation of p53, and suggest that hesperidin may be a promising candidate for the treatment against dexamethasone-induced osteoporosis.